Establishment of Urochloa brachyura</i)(Hack.) Stapf and its potential role in planted pastures and reclamation - Rethman, N.F.G. (University of Pretoria, 2013)
Dissertation (MSc (Pasture Management))--University of Pretoria, 2007.